Facial Arterial Depth and Relationship with the Facial Musculature Layer. Issue 2 (February 2015) - Lee, Jae-Gi; Yang, Hun-Mu; Choi, You-Jin; Favero, Vittorio; Kim, Yi-Suk; Hu, Kyung-Seok; Kim, Hee-Jin
<x xml:space="preserve">Abstract</x> Background: Previous studies have revealed a variation in the origin and distribution patterns of the facial artery. However, the relationship between the facial artery and the facial muscles has not been well described. The purpose of this study was to determine the facial artery depth and relationship with the facial musculature layer, which represents critical information for dermal filler injection and oral and maxillofacial surgery. Methods: Fifty-four embalmed adult faces from Korean cadavers (36 male and 18 female cadavers; mean age, 73.3 years) were used in this study. A detailed dissection was performed, with great care being taken to avoid damaging the facial artery underlying the facial skin and muscle. Results: The facial artery was first categorized according to the patterns of its final arterial branches. The branching pattern was classified simply into three types: type I, nasolabial pattern (51.8 percent); type II, nasolabial pattern with an infraorbital trunk (29.6 percent); and type III, forehead pattern (18.6 percent). Each type was further subdivided according to the facial artery depth and relationship with the facial musculature layer as types Ia (37.0 percent), Ib (14.8 percent), IIa (16.7 percent), IIb (12.9 percent), IIIa (16.7 percent), and IIIb (1.9 percent). Conclusion: This study provides new anatomical insight into the relationships between the facial artery branches and the facial muscles, including providing useful information for clinical applications in the fields of oral and maxillofacial surgery.